2015
DOI: 10.1134/s1070328415070027
|View full text |Cite
|
Sign up to set email alerts
|

New μ-OAC bridged dinuclear copper(II) complex with tridentate Schiff base ligand: Synthesis, characterization, crystal structure, and CuO nano-particles formation

Abstract: A new (μ acetato) bridged dinuclear copper(II) complex [Cu 2 (L) 2 (μ OAc) 2 ] (I) has been synthe sized by the reaction of a tridentate N 2 O Schiff base ligand (HL) with Cu(OAC) 2 in methanol at refluxed con ditions and characterized by elemental analysis (CHN) and FT IR spectroscopy. The crystal structure of I was investigated by single crystal X ray diffraction (CIF file CCDC no. 1013907). X ray results showed that two OAC groups bridge the copper(II) ions in a Cu 2 O 2 core of a binuclear complex. Each co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…For instance, Oshin and co‐workers reported that the bond length of Cu−Cl (2.27–2.28 Å) was shorter than that of Cu−O from ClO 4 − ion (2.78 Å) or CF 3 SO 3 − ion (2.53 Å) in analogous copper complexes [13b] . Also, it has been reported that the OAc − ion can serve as bridging ligand in copper complexes with relatively short bond length (1.94–1.96 Å) [13e,f,14] …”
Section: Resultsmentioning
confidence: 99%
“…For instance, Oshin and co‐workers reported that the bond length of Cu−Cl (2.27–2.28 Å) was shorter than that of Cu−O from ClO 4 − ion (2.78 Å) or CF 3 SO 3 − ion (2.53 Å) in analogous copper complexes [13b] . Also, it has been reported that the OAc − ion can serve as bridging ligand in copper complexes with relatively short bond length (1.94–1.96 Å) [13e,f,14] …”
Section: Resultsmentioning
confidence: 99%